Linking the social economy and green growth in Costa Rica under a multiple case study (National Administration Journal, 2021)
Costa Rica is a leader in environmental topics and has a consolidated social economy. The social economy and green growth can be a viable combination to reach sustainability. This research seeks to know, through a study of multiple cases with four cooperatives, one solidarity association and a savings bank, if the undertaken green actions and the sustainable benefits that were obtained have promoted positive impacts on these organizations; inquires if these processes were financed through green financial tools. The obtained results showed that there is a link between green growth and the cases studied, although it was detected that there are aspects to be improved, such as the protection of biodiversity. In addition, benefits are perceived for thegreen actions carried out, but it is observed that there is a limited use of green financial tools, which implies that green growth could be enhanced if they were implemented.
Keywords: Sustainability; cooperatives; solidarism; ethics banking; global warming; ecosystemic resources; financial green funds